Advertising in "La Moda Elegante" during the interwar period (1918- 1927) - Arroyo Martín, Carmen (Revista General de Información y Documentación, 2018)
The advertisements published in newspapers and magazines became a key source of funding for the continuity of many publications during the nineteenth century and the first decades of the twentieth century when the income from subscriptions became insufficient. Beauty and aesthetic ads published in women’s and fashion magazines were the most common and were related to the contents published and their audience. This article analyzes the advertisements inserted in the interwar period 1918-1927 in La Moda Elegante, one of the most important and longest-standing specialized magazines published in Spain. Like the rest of specialized journals had a clear French influence that was reflected both in design and in the contents. This study on advertising of La Moda Elegante allows us to know the evolution in tastes and trends, as well as social changes during the interwar period which was a turning point in the role assigned to women and women’s clothing.